Case study: Correction of angular deformity post-trans-tibial amputation to improve prosthesis fit and comfort. (April 2015) - Lineham, Beth; Harwood, Paul; Giannoudis, Peter
Background: This case report describes the revision of a trans-tibial amputation complicated by a proximal malunited fracture. It demonstrates the complexity of decisions involved in revisions of this nature. Case description and methods: The patient presented has a painful stump due to breakdown of soft tissues. She had been suffering for over a year with pressure sores and inability to use a prosthesis resulting from this, decreasing her quality of life. Malunion of a tibial fracture proximal to the amputation complicated her condition. Findings and outcomes: Initially it was feared that the amputation level would be converted to a through-knee amputation, but wedge osteotomy of the tibia allowed coverage of the stump, increasing functionality for the patient, while still maintaining a below-knee stump. Conclusion: This report highlights the importance of addressing the cause of soft tissue problems in an amputation revision, which must be addressed on a case-by-case basis. Clinical relevance: This case offers an insight into the decision-making process in limb reconstruction and suggests a solution for similar cases. It is important that all surgical options are considered before amputation length is sacrificed.